Plan operativo anual: POA 1996 / 97 - Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL) (1996)
Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL)